2022
DOI: 10.1093/hmg/ddac167
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of KBG syndrome in a large European cohort

Abstract: KBG syndrome is characterised by distinctive facial gestalt, short stature and variable clinical findings. With ageing, some features become more recognizable, allowing a differential diagnosis. We aimed to better characterise natural history of KBG syndrome. In the context of a European collaborative study, we collected the largest cohort of KBGS patients (49). A combined array-CGH and NGS approach investigated both genomic CNVs/SNVs. Intellectual disability (ID) (82%) ranged from mild to moderate with severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The prenatal and neonatal results of our cohort mirror those reported in past KBG cohorts. In a previous Northern European cohort of 49 individuals, 16% of participants had congenital heart defects, including ASD, VSD, and valvular insufficiencies (Loberti et al, 2022). 10.2% of participants had arachnoid cysts, 23% of participants had an enlarged cisterna magna, and other participants had periventricular nodular heterotopia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prenatal and neonatal results of our cohort mirror those reported in past KBG cohorts. In a previous Northern European cohort of 49 individuals, 16% of participants had congenital heart defects, including ASD, VSD, and valvular insufficiencies (Loberti et al, 2022). 10.2% of participants had arachnoid cysts, 23% of participants had an enlarged cisterna magna, and other participants had periventricular nodular heterotopia.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding difficulties were commonly seen in this cohort. In terms of prenatal findings, 28.5% had antenatal ultrasound abnormalities, including nuchal translucency, polyhydramnios, and intrauterine growth restriction (Loberti et al, 2022). Another cohort of 45 individuals reported 31.3% with feeding difficulties, 9% with congenital heart defects, and 28% of participants with cryptorchidism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have noted that haploinsufficiency is the likely pathogenic mechanism in these cases based on the tightly regulated abundance of ANKRD11 during the cell cycle (Walz et al, 2015). Moreover, molecular analysis of cohorts of patients with KBG syndrome have found that the majority of ANKRD11 pathogenic variants are frameshift and nonsense variants leading to a loss‐of‐function, and presumably, haploinsufficiency as well (Gnazzo et al, 2020; Goldenberg et al, 2016; Loberti et al, 2022; Low et al, 2016; Parenti et al, 2021; Scarano et al, 2019). Recenty, functional studies performed on ANKRD11 missense variants found these decreased ANKRD11 stability and transcriptional activity, further supporting haploinsufficiency as a pathologic mechanism for KBG syndrome (de Boer et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Seizures occurred in three patients (3/8, 37.5%), and abnormal EEG findings were observed in two patients (2/8, 50%), including one who did not show clinical findings of seizure. Prior to the recently published European large‐scale cohort paper (Loberti et al, 2022 ), the comorbidity rate of brain malformations in patients with KBG syndrome was not known precisely. It reported that 32 out of the total 49 cohort patients underwent brain MRI, and cerebral abnormalities were found in more than half of them (18/32, 56.3%).…”
Section: Discussionmentioning
confidence: 99%